Automatic Screen Reader Using JITBIT for Sending Message on WhatsApp Messenger - Alam Rahmatulloh; Faisal Muhammad Dzikry; Rahmi Nur Shofa; Randi Rizal (Journal of Innovation Information Technology and Application (JINITA), 2023)
The current sales trend uses more online transaction concepts. The use of digitalization in online transactions and marketing is very important for businesses in increasing sales results to the maximum and on target. One way to increase this is by promoting on social media such as WhatsApp. Limited consumer contact makes it difficult for business actors to carry out promotions, so a database of consumer contacts is needed that can be maximized. In addition, problems in the process of sending manual messages can be overcome by using automatic message-sending actions so that promotions can be carried out automatically and quickly. The sending process is assisted by an "IF-THEN" statement and a screen that can recognize color conditions so that the automatic action can be operated on other services. The main objective of this research is to create a service that can accommodate consumer contacts by sharing contacts between business actors and being able to send messages automatically on WhatsApp by utilizing JITBIT. The results of this study prove that using JITBIT can send messages automatically on WhatsApp and can be operated on other services such as web-based applications. The results of the tests that have been carried out show that the accuracy level of JITBIT can send messages 100% with a delivery speed of 12 – 12.39 seconds/message